ANALYSIS OF THE RESULTS OF THE TOGEL GAMBLING CRIMINAL TRIAL IN THE GROBOGAN COMMUNITY (Case Study at the Purwodadi District Court) - Nur Oktavia, Fera Dyah; Gunarto, Gunarto (Jurnal Hukum Khaira Ummah, 2023)
This research background of gambling case in Grobogan society which increasingly rampant and disturbing society. The juridical guidelines in this case refer to the Criminal Code in Article 303 paragraph (3) amended by Act Number 7 of 1974 concerning Gambling Control. Gambling contains three main elements as the main features of the game (race), the chances and the bet. The formulation of this thesis problem includes: (1) How are criminal sanctions against perpetrators of Gambling Crimes according to Positive Criminal Law at this time? (2) How is the application of criminal sanctions against perpetrators of the Togel Gambling in Purwodadi District Court? (3) What is the consideration for the judge in deciding the Crime of Gambling Togel in Purwodadi District Court? The purpose of this research is to know and explore: (1) criminal sanction against perpetrator of Gambling Crime according to Positive Criminal Law at this time. the application of criminal sanctions against perpetrators of the Toll of Togel gambling. (3) consideration for judges in deciding the Crime of Gambling Togel in Purwodadi District Court. The authors collected data, using interview techniques to judges who decided the case of gambling in the Purwodadi District Court. The research resulted in the findings of legal facts, namely: (1) In accordance with the decision Number 09 / Pid.B / 2017 / PN PWD Article 303 paragraph 3 of the Criminal Code, the Public Prosecutor has filed a 10-month imprisonment, but the Court Judge State of Purwodadi give demands to the Defendants is lighter ie Criminal Criminal for 6 (six) months. (2) The application of legal certainty, the Prosecutor shall ensure the Defendant through examination of the evidence contained in a copy of the above court decision with Article 303 paragraph (1) of the Criminal Code jo article 55 paragraph (1) of the Criminal Code and prosecuted for 10 (ten) months minus the period of detention, while the Panel of Judges decide cases based on consideration given the provisions, Law no. 8 of 1981 and the relevant articles and rules, the Defendants were sentenced to 6 (six) months imprisonment. (3) Judge consideration in deciding cases is a gambling game based on the expectation of winning in general depending on the luck alone, the greater expectation gives birth to the element of speculation in the game and this is not authorized by the authorities based on the disturbing nature of society.Keyword : Gambling Crime, the Criminal Code in Article 303, Criminal Cage